2017
DOI: 10.1098/rsta.2016.0176
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of drill bit drop tests on Kuru granite

Abstract: One contribution of 15 to a theme issue 'Experimental testing and modelling of brittle materials at high strain rates'. This paper presents an experimental and numerical study of Kuru grey granite impacted with a sevenbuttons drill bit mounted on an instrumented drop test machine. The force versus displacement curves during the impact, so-called bit-rock interaction (BRI) curves, were obtained using strain gauge measurements for two levels of impact energy. Moreover, the volume of removed rock after each drop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Other examples are the blasting of limestone rock in open quarries for the production of aggregates and sand where controlling the block size distribution is an important objective (figure 1b) [2] or the working of rocks in the mining industry. The use of percussive drilling tools in civil engineering constitutes an application in which the understanding and numerical modelling of the damage processes is essential as shown in figure 1c [3,15,16]. The influence of pre-existing cracks on the dynamic tensile strength of granite at high strain rates also constitutes an important topic [17,18].…”
Section: Brittle Materials: Materials Widely Exposed To Dynamic Loadingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are the blasting of limestone rock in open quarries for the production of aggregates and sand where controlling the block size distribution is an important objective (figure 1b) [2] or the working of rocks in the mining industry. The use of percussive drilling tools in civil engineering constitutes an application in which the understanding and numerical modelling of the damage processes is essential as shown in figure 1c [3,15,16]. The influence of pre-existing cracks on the dynamic tensile strength of granite at high strain rates also constitutes an important topic [17,18].…”
Section: Brittle Materials: Materials Widely Exposed To Dynamic Loadingsmentioning
confidence: 99%
“…Among the constitutive models developed to numerically simulate the response of brittle materials are the modified version of the HJC model (MHJC) [54] inspired by the Holmquist-Johnson-Cook (HJC) model [55] which is applied to numerically simulate a drill bit drop test against Kuru granite rock [16]. Furthermore, an improved model is proposed for glass that represents both its interior and surface strength so that the numerical approach can be used to simulate single or multi hit situations for transparent windshields [56].…”
Section: Modelling and Numerical Methods Dedicated To Brittle Materialsmentioning
confidence: 99%
“…e rock cuttings are discharged by using flushing water or air. Under the action of propulsion provided by the hydraulic cylinder, the drill continuously impacts, rotates, and discharges rock cuttings to form the blast hole [4,5]. e working principle is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Lundberg and Collet [15] pursued an optimal incident wave for maximizing the efficiency of the conversion of wave energy into rock breakage under indenter impact. Fourmeau et al [16] presented experimental and numerical research on rock breakage by a multi-indenter bit and found that the confining pressure has an effect of an approximately 10% decrease in the rock breakage volume. Aziznejad et al [17] adopted the distinct element code (PFC2D) to investigate the rock fracture under impact loading, and the numerical results are very consistent with the experiments.…”
Section: Introductionmentioning
confidence: 99%